2023
DOI: 10.47577/technium.v11i.9132
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Blockchain Technology in Various Applications to Secure Data Flows. A Comprehensive Analysis

Abstract: Blockchain technology has emerged as a disruptive force in the world of digital transactions, with applications across a wide range of industries. This paper provides a comprehensive review of the potential applications of blockchain technology, including finance, healthcare, supply chain management, and voting. The paper discusses the benefits and challenges of using blockchain technology, as well as real-world case studies of its implementation. The paper concludes with suggestions for future research, explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The study examined the impact of personality traits and motivational factors on the performance of crucial managers within marketing companies. The study's findings indicated that individuals with a learning and performance orientation tend to exhibit enhanced problem-solving abilities (Halkiopoulos et al, 2023c). Extroversion, cooperativeness, conscientiousness, and emotional stability strongly correlate with motivation.…”
Section: Resultsmentioning
confidence: 84%
“…The study examined the impact of personality traits and motivational factors on the performance of crucial managers within marketing companies. The study's findings indicated that individuals with a learning and performance orientation tend to exhibit enhanced problem-solving abilities (Halkiopoulos et al, 2023c). Extroversion, cooperativeness, conscientiousness, and emotional stability strongly correlate with motivation.…”
Section: Resultsmentioning
confidence: 84%
“…The included research and articles, as well as what we studied in general, offer much information about the development and evolution of personality and the extent to which genetic and environmental factors influence it. Some published articles still needed to provide comprehensive research or were still in progress; therefore, they were not included (Halkiopoulos et al, 2023c). In general, the study of personality is a complex issue, and researchers have yet to conclude which factor is most responsible for its development.…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigation is required to gain a more comprehensive understanding of the intricacies of this association and its ramifications within the professional environment (Gkintoni et al, 2016;Gkintoni et al, 2017). Subsequent investigations may examine the ramifications of emotional intelligence across various occupational domains, encompassing creativity, collaboration, resilience under stress, employee contentment, and innovation (Halkiopoulos et al, 2022;Halkiopoulos et al, 2023c). An alternative proposition entails the creation of educational initiatives targeting the enhancement of emotional intelligence within professional settings (Gkintoni et al, 2021b;Gkintoni et al, 2021c).…”
Section: Discussionmentioning
confidence: 99%